Induced systemic resistance against Botrytis cinerea by Micromonospora strains isolated from root nodules - Martínez-Hidalgo, Pilar; García, Juan M.; Pozo, María J. (Frontiers in Microbiology, 2015)
Micromonospora is a Gram positive bacterium that can be isolated from nitrogen fixing nodules from healthy leguminous plants, where they could be beneficial to the plant. Their plant growth promoting activity in legume and non-legume plants has been previously demonstrated. The present study explores the ability of Micromonospora strains to control fungal pathogens and to stimulate plant immunity. Micromonospora strains isolated from surface sterilized nodules of alfalfa showed in vitro antifungal activity against several pathogenic fungi. Moreover, root inoculation of tomato plants with these Micromonospora strains effectively reduced leaf infection by the fungal pathogen Botrytis cinerea, despite spatial separation between both microorganisms. This induced systemic resistance, confirmed in different tomato cultivars, is long lasting. Gene expression analyses evidenced that Micromonospora stimulates the plant capacity to activate defense mechanisms upon pathogen attack. The defensive response of tomato plants inoculated with Micromonospora spp. differs from that of non-inoculated plants, showing a stronger induction of jasmonate-regulated defenses when the plant is challenged with a pathogen. The hypothesis of jasmonates playing a key role in this defense priming effect was confirmed using defense-impaired tomato mutants, since the JA-deficient line def1 was unable to display a long term induced resistance upon Micromonospora spp. inoculation. In conclusion, nodule isolated Micromonospora strains should be considered excellent candidates as biocontrol agents as they combine both direct antifungal activity against plant pathogens and the ability to prime plant immunity.